Optimisation of biomass, exopolysaccharide and intracellular polysaccharide production from the mycelium of an identified ganoderma lucidum strain qrs 5120 using response surface methodology - Supramani S.; Ahmad R.; Ilham Z.; Annuar M.S.M.; Klaus A.; Wan-Mohtar W.A.A.Q.I. (AIMS Press, 2024)
Indexed by WOS/ Scopus